Resiliência e estrutura de uma comunidade arbórea em floresta estacional decidual no sul do Brasil - Missio, Francieli de Fátima (2019)
Forests in Rio Grande do Sul have large proportions of fragmented areas, mainly due to agricultural and livestock activities which require studies to increase knowledge about the dynamics of these formations. Therefore, the objective of this work was to evaluate the structure and floristic composition in conjunction with environmental variables and ecological configurations, in a secondary forest environment in Dona Francisca, RS, Brazil. For this purpose, 50 plots measuring 10 m x 20 m (200 m²) were spaced 10 m apart in 10 parallel strips, 40 m apart, from the base to the top of the slope, with a total sampling area of 1 ha forest. Adult individuals were identified and the dendrometric variables, DBH and height were measured. From the environmental variables were collected those related to the soil, topography and luminosity. And for the ecological strategies of plants were determined the functional traits related to leaf, maximum DBH, maximum height, regeneration guilds and dispersion syndrome. From the analyzes and correlations, it was possible to verify 2.045 individuals distributed in 65 tree species distributed in 31 botanical families, with distribution in the most initial dap classes, indicating a young population. Casearia sylvetris was the species of greatest abundance with 505 individuals, followed by Nectandra lanceolata, Cupania vernalis and Guarea macrophylla, in importance value. Seven exotic species were sampled, which totaled 105 individuals. Of these Hovenia dulcis presented 85 individuals. The environmental variables correlated with the distribution of the species were those related to relief, canopy cover and phosphorus content, influencing the tree community structure. In addition, Hovenia dulcis and canopy cover showed a negative correlation, which may be a determining factor in the growth of its population, since the species needs light for its life cycle. From the functional traits, the main species were grouped in conservatives and acquisitions, being the most numerous, reinforcing that the forest is regenerating before the ecological and environmental conditions. Also that the functional traits dispersion syndrome and regeneration guilds are important strategies of plants for the restoration of native vegetation in area after agricultural cultivation. The functional attributes that presented negative correlation were leaf area and specific and positive leaf area between maximum diameter and maximum height, both correlations corresponding to plant growth and development. In this sense, the study area presented characteristics of a forest in the regeneration stage with the capacity to restore native vegetation, being resilient even presenting exotic species. Thus, it is very important to accompany secondary forests in formation, since they allow inferring in the composition of forest formations to a greater basis for their conservation and preservation in the State of RS.